Development and evaluation of a customizable electron-ic medical record for clinical outcomes research and patient engagement - Miller, Wayne; Patton, Jennifer; Lally, Patricia; Cusick-Lewis, Joshua; Fitzpatrick, Karen; Heinsberg, Haylee (International Journal of Medicine, 2016)
Background: Electronic Medical Records (EMRs) provide a database to support clinical information needs. However, it is often difficult to access EMR-generated data to answer specific clinical-based questions. Furthermore, EMR is not designed to complete the circle of care by interacting and communicating directly with patients. The problem is even greater in rural practices, with limited resources, and with providers inexperienced in research, who are doing well to meet the daily requirements of keeping their practice doors open.Objective: Design and evaluate a customizable EMR-Reporting Tool (EMR-RT) that can be used as an adjunct to an existing EMR or as a sole-standing EMR-RT for clinical outcome's research and patient engagement.Methods: Two rural and two urban family practice clinics participated in the design and beta testing of a customizable EMR-RT for clinical effectiveness research and for patient engagement. The EMR-RT was implemented in each clinic for a 6-month clinical trial.Results: The EMR-RT used in each clinic was simplistic enough that community health workers could handle patient data entry, data management, and data extraction independently. Each clinic could incorporate clinic-specific measurement variables into the EMR-RT database with minimal effort. Changes to the EMR-RT database capabilities could be performed off-site through the Internet.Conclusions: A customizable EMR-RT was successfully designed and implemented in two rural and two urban family practice clinics. The EMR-RT was robust enough to congregate clinical research data, but flexible enough and simplistic enough that workers who were previously untrained in EMR use could quickly utilize the system.